Zastosowanie treningu neurofeedback w pracy z dziećmi z niepełnosprawnością intelektualną w stopniu lekkim. Projekt procedury - Rochatka, Weronika (Studia Edukacyjne, 2021)
As a method of training neurofeedback has proved to be effective in education and therapy of children (e.g., with ADHD, autism spectrum or specific learning disorders). However, there are no neurofeedback training protocols targeting individuals with a mild intellectual disability. Therefore, I designed a neurofeedback procedure for children with this disability; it focuses on attention span training. In this study I presented the pre-planned procedure to the child’s parent to determine whether the proposed method is feasible for work with a child with a mild intellectual disability. After learning the parents’ opinion, I indicate the possible further stages of developing a neurofeedback strategy for working with children with a mild intellectual disability. Finally, I demonstrate the future directions of research and planning of neurofeedback procedures for individuals with special needs.